Harnessing artificial intelligence and remote sensing in climate-smart agriculture: the current strategies needed for enhancing global food security - Gideon Sadikiel Mmbando (Cogent Food & Agriculture)
Global food security is seriously threatened by climate change, which calls for creative agricultural solutions. However, little is known about how different smart technologies are integrated to enhance food security. As a strategic reaction to these difficulties, this review investigates the incorporation of remote sensing (RS) as well as artificial intelligence (AI) into climate-smart agriculture (CSA). This review demonstrates how these advances can improve agricultural resilience, productivity, and sustainability by utilizing AI’s capacity for predictive analytics, crop modelling, and precision agriculture, along with RS’s strengths in climate projections, land management, and continuous surveillance. Several important tactics were covered, such as combining AI and RS to regulate risks, maximize resource utilization, and enhance agricultural practice choices. The review also discusses issues like policy frameworks, capacity building, and accessibility that prevent these technologies from being widely adopted. This review highlights how AI and RS can further CSA and offers insights into how they can help ensure food systems remain secure in changing climates.